2014
DOI: 10.1097/pec.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an After-Hours Call Center

Abstract: Our study identifies that a third of unnecessary pediatric visits to the ED occurred as a result of the nurse triage telephone system in question. We recommend review of the algorithms stated to reduce strain on local ED resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…These concerns exist due to the potentially fatal consequences of underestimating the urgency of a child’s condition, the nonspecific nature of many childhood illnesses, the speed with which children deteriorate, and the lack of face-to-face contact, forcing assessors to depend on caregivers to observe the child, interpret those observations, and communicate them effectively [57,5961,64]. The safety of CDS software used to triage children over the telephone is unclear, particularly its sensitivity to detect signs of serious illness in children [53,6062,6568], although its purpose is to minimize risk by standardization and to reduce assessor autonomy—a factor underlying many incidents [61,62]. …”
Section: Discussionmentioning
confidence: 99%
“…These concerns exist due to the potentially fatal consequences of underestimating the urgency of a child’s condition, the nonspecific nature of many childhood illnesses, the speed with which children deteriorate, and the lack of face-to-face contact, forcing assessors to depend on caregivers to observe the child, interpret those observations, and communicate them effectively [57,5961,64]. The safety of CDS software used to triage children over the telephone is unclear, particularly its sensitivity to detect signs of serious illness in children [53,6062,6568], although its purpose is to minimize risk by standardization and to reduce assessor autonomy—a factor underlying many incidents [61,62]. …”
Section: Discussionmentioning
confidence: 99%
“…Of the 15 other studies, 72,89,100,101,[115][116][117][118][119]124,131,135,[138][139][140] four studies looked at the appropriateness of ED referrals. In terms of referral sources, no difference was found between telephone and self-referred patients, 118 but doctor-referred patients were the most appropriate referrals.…”
Section: Service Impactsmentioning
confidence: 99%
“…In terms of referral sources, no difference was found between telephone and self-referred patients, 118 but doctor-referred patients were the most appropriate referrals. 117 One study identified 33% of ED referrals as non-essential 139 and another identified that a high proportion of ED referrals should have been handled in primary care. 116 Most studies reported that a high proportion of referrals, often in excess of 90%, were appropriate.…”
Section: Service Impactsmentioning
confidence: 99%
“…The pandemic telemedicine model differs from the traditional consumer-driven one in which health care providers and a growing number of telemedicine venders offer a service designed to appeal to, and be chosen by, those who are most comfortable using technology as an enhancement to their lives. 20–23 The speed and convenience are geared to patients who will self-select telemedicine. By contrast, the COVID-19 pandemic and social distancing requirements resulted in a model in which the driver is a set of external conditions.…”
Section: Discussionmentioning
confidence: 99%